2015
DOI: 10.1016/j.laa.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Lovász theta type norms and operator systems

Abstract: Abstract. To each graph on n vertices there is an associated subspace of the n × n matrices called the operator system of the graph. We prove that two graphs are isomorphic if and only if their corresponding operator systems are unitally completely order isomorphic. This means that the study of graphs is equivalent to the study of these special operator systems up to the natural notion of isomorphism in their category. We define new graph theory parameters via this identification. Certain quotient norms that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Recall [12] that the operator system of a graph G on n vertices is the subspace of the n × n complex matrices M n given by…”
Section: Quantum Homomorphisms and Cp Mapsmentioning
confidence: 99%
“…Recall [12] that the operator system of a graph G on n vertices is the subspace of the n × n complex matrices M n given by…”
Section: Quantum Homomorphisms and Cp Mapsmentioning
confidence: 99%
“…In this section, we examine inductive limits of graph operator systems, viewing them as the operator systems of topological graphs via the theory of topological equivalence relations [34]. We identify the C*-envelope of such an operator system, and prove an isomorphism theorem; these can be viewed as a topological version of recent results from [28]. We also establish a version of the Glimm Theorem for this class of operator systems.…”
Section: Inductive Limits Of Graph Operator Systemsmentioning
confidence: 99%
“…In Section 6, we consider inductive limits of graph operator systems. This class of operator systems was introduced in [11] and subsequently studied in [28], where the authors showed that the graph operator system is a complete isomorphism invariant for the corresponding graph, and identified its C*-envelope. In view of the importance of graph operator systems in Quantum Information Theory, where they correspond to confusability graphs of quantum channels [11], we establish inductive limit versions of the aforementioned results.…”
Section: Introductionmentioning
confidence: 99%
“…It is not known whether the converse is true or not. However, motivated by the discussions in [19,Section 3], we obtain the following characterization of the (min, max)-nuclear graph operator systems.…”
Section: Nuclearity Of Graph Operator Systemsmentioning
confidence: 99%
“…In Section 6, we characterize (min, max)-nuclear graph operator systems (as introduced in [15]) for finite graphs, purely in terms of graph-theoretic properties. We achieve this characterization using an identification of their C * -envelopes obtained in [19].…”
Section: Introductionmentioning
confidence: 99%